2021
DOI: 10.53853/encr.7.4.655
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad y seguridad de tocilizumab en 2 casos de orbitopatía tiroidea grave refractaria a corticosteroides. Hospital San José, Bogotá

Abstract: La orbitopatía tiroidea es la manifestación extratiroidea más frecuente del hipertiroidismo autoinmune; más del 90 % de los casos se asocian con enfermedad de Graves (EG). Es un trastorno complejo que puede provocar deformidad orbitaria, visión doble e incluso pérdida visual permanente, con gran impacto en la calidad de vida. Aproximadamente, el 2 % de los pacientes que desarrollan orbitopatía de Graves desarrolla enfermedad moderada a grave. Existe una creciente conciencia de la necesidad de un diagnóstico pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Most studies are case reports or case series. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Only one randomized clinical trial has been published, 44 and the remaining reports include a prospective interventional nonrandomized study, 45 2 observational 46,47 an open-label multicenter, 48 and a retrospective longitudinal study. 49 Table 2 shows the 2 comparative studies found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies are case reports or case series. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Only one randomized clinical trial has been published, 44 and the remaining reports include a prospective interventional nonrandomized study, 45 2 observational 46,47 an open-label multicenter, 48 and a retrospective longitudinal study. 49 Table 2 shows the 2 comparative studies found.…”
Section: Resultsmentioning
confidence: 99%
“…44,47 The total number of patients in all studies was 208. Fifteen reports originated from European centers, 27,30,31,34,36,45,46,48,[50][51][52][53][54][55] 6 studies were conducted in the United States, 28,29,32,39,56,57 2 in Colombia, 35,58 2 in the United Arab Emirates, 38,59 and 1 in Mexico. 33 There were 2 multicentric reports.…”
Section: Resultsmentioning
confidence: 99%